Factors influence switching behavior of Islamic bank customers : does syariah issue matter? - Abduh, Muhamad; Kassim, Salina; Dahari, Zainurin (2012)
An Islamic bank is now not only facing competition from its peer Islamic banks but also from conventional bans, which offer Islamic banking products through their Islamic subsidiary. When the competition becomes tougher, customers are given more options to choose their banks and switch from their current bank to other Islamic banks. Thus, the objective of this study is o evaluate factors influence the switching behavior of Islamic banking customers, in the case of Malaysia, based on the syariah compliance issues. Using logistic regression, the results show that the customer’s religion, type of account, and whether or not they have account in conventional bank are the significant factors to influence their switching behavior when they encounter non-syariah products and practices in their Islamic bank.